THE OCCURRENCE OF INTRACELLULAR CHONDROITIN SULFATE - Thorp, Frank K. (The Rockefeller University Press, 1963)
Suspensions of chondrocytes were prepared by treatment with trypsin of the epiphyses of tibias and femurs of 13-day-old chick embryos. After washing to remove the matrix, such suspensions readily incorporate radioactive sulfate into both intracellular and extracellular chondroitin sulfate. Following disruption of the cells, the cell constituents were fractionated by centrifugation. Fractions obtained from cells incubated for 10 minutes showed a concentration of radioactivity in the material which sediments at 10,000 to 20,000 g. At this time the radioactivity of the extracellular chondroitin sulfate is low, but at 1 hour the radioactivity of the intracellular material is relatively unchanged, while that of the extracellular polysaccharide is markedly increased. Following incubation of the chondrocyte suspensions in a tissue culture medium, the intracellular chondroitin sulfate was isolated. This was compared with chondroitin sulfate isolated from the cartilage matrix. Chemical analysis and infrared spectroscopy indicated that both the intracellular and extracellular polysaccharides consist of a mixture of chondroitin sulfuric acids A and C. A portion of the chondroitin sulfate is not sulfated.